Determinants of consumers’ purchase intentions of organic vegetables: some insights from Malaysia - Norazah Mohd Suki (Taylor & Francis Group, 2017)
This study tests the mediating effects of corporate social responsibility (CSR), product image, and corporate reputation on the relationships between green marketing awareness and consumers’ purchase intentions of organic vegetables. Data from 200 valid questionnaires was analyzed utilizing a partial least squares approach. Results show that product image was confirmed as the leading factor that partially mediated the influence of consumer green marketing awareness on consumers’ purchase intentions of organic vegetables, and this was followed by CSR, but that corporate reputation was not established as a mediator. Marketing managers should, therefore, develop various effective strategies to communicate their companies’ product image, embracing green marketing practices in order to increase market awareness, and providing positive recommendations to friends and relatives via various marketing communication channel including the short message service (SMS), emails, and social networking sites (SNS).